Development of a targeted drug delivery system for the treatment of hepatitis C virus infection - Baloch, Baby Kanwal (2012)
Background: Hepatitis C virus infection affects more than 170 million people worldwide and is frequently associated with chronic liver disease and hepatocellular carcinoma. No protective vaccine is yet available and the current standard of care, consisting of pegylated interferon alpha and ribavirin, has limited efficacy. Ribavirin is a key component of any effective anti-HCV regimen. However, accumulation of ribavirin in the red cell compartment not only reduces drug efficacy as a result of diversion to extra-hepatic sites but also produces haemolytic anaemia which can lead to dose reduction or discontinuation of treatment. Lipid or polymer based nanoparticles can be used to deliver therapeutic agents, such as drugs or small interfering RNAs (siRNAs) directly to their site of action. We therefore elected to develop new antiviral strategies based on the targeted delivery of ribavirin to hepatocytes, coupled with the identification of new therapeutic targets. In order to inform the rational use of direct intracellular delivery of ribavirin, we enquired whether variation in expression of the ribavirin transporter may determine drug uptake and permit the identification of individuals who would benefit from these alternative approaches to treatment.